Akibat Hukum Pembatalan Akta Hibah Yang Dibuat Di Bawah Tangan Dan Tanpa Persetujuan Ahli Waris Lainnya (Lex Jurnalica, 2023)
A grant is a gift made by a person to another party made while still alive and the implementation of the distribution is usually done when the grantor is still alive. In Article 1682 of the Civil Code